A EFA Analysis of Digital Technology Teaching Materials in Improving Students' Critical Thinking in Physics Learning - Lintangesukmanjaya, Rahmatta Thoriq; Mahendra, Agusti; Anugrah, Sherlynggar; Prahani, Binar Kurnia; Dwikoranto, Dwikoranto; Satriawan, Muhammad; Rizki, Iqbal Ainur (Universitas Negeri Surabaya, 2024)
Objective: The research aims to analyze the effectiveness of physics learning by applying technology or digital teaching materials significantly to improve students' critical thinking abilities. Knowledge regarding the need to use digital technology in educational institutions today can be used to implement innovative learning plans in the future. Method: The research was carried out using quantitative descriptive methods based on the data that had been obtained. Statistical tests in research involve the analysis of student response questionnaire results and literature reviews. Analysis of case study questionnaire responses on using technology in learning and the media needs of 92 students were analyzed using Exploratory Factor Analysis (EFA). Results: Based on the case study analysis obtained using EFA analysis, the need for learning using digital technology is very high. The response of students' motivation and interest in future learning received the maximum response that students need interactive learning with the help of engaging digital media, one of which is virtual simulation, which is relevant in improving critical thinking skills. Novelty: Application of Exploratory Factor Analysis (EFA) to analyze students' needs for digital media to improve critical thinking skills in physics learning. With support, the literature review shows a relevant relationship between the needs and challenges of developing technology in current digital learning media in providing an impact on alternative aspects of cost, time, space, and security to improve critical thinking skills. This research can be used to plan innovative learning in the future.